Self-Directed Learner The Three Pillar Model for developing self- directedness - Gavriel, Jennifer (Taylor & Francis, 2005)
Self-directed learning is a buzz term that has been used within educational circles for some time now. An educator wants their students to fulfill their potential and work to the maximum of their abilities. As with younger students, the challenge with teaching adults is to encourage discipline and focus in studying and to develop a motivation for learning as opposed to simply seeking the answers. This book captures the frustrations involved in this pursuit and provides strategy and solutions for both educator and student alike. Using the three pillar model, the foundation for life-long, self-directed learning is clearly outlined and encouraged through a focus on skills, motivation and self-belief.